Development of diagnostic assays for emergent RNA viruses - Wu, Ge (2020)
This study aims to develop novel diagnostic assays for zika virus (ZIKV) and equine influenza viruses (EIV) by • Generating pseudotyped ZIKV as a surrogate for wild-type virus in the virus neutralisation (VN) test • Producing plant-expressed ZIKV non-structural (NS) 1 protein as a surrogate for wild-type virus in the ELISA • Identifying lineage-specific antibodies against EIV using Next Generation Phage Display (NGPD) to replace antibodies produced by immunizing animals for use in ELISA.